Infant feeding practices of a tribal community in a mandal of Khammam district, Telangana - Alwala, Rajeshwar Rao; Dudala, Shankar Reddy; Bolla, Chandrasekhar Reddy; Patki, Manoj B.; Ravi Kumar, B. P. (International Journal Of Community Medicine And Public Health, 2018)
Background: Breast milk is the best, safest and most nutritious food for infants. Though breast feeding is almost universal, there are yet some myths and false beliefs surrounding the practice due to various cultures and traditions in India. In the present study an attempt was made to understand various aspects of infant feeding practices among the Sugali tribes of Khammam district, Telangana state. Methods: A cross sectional study was conducted among Sugali community in Khammam mandal of Khammam district in Telangana from March to June 2010. In which 314 families with pre-school children were interviewed using a pre–designed semi-structured questionnaire. Results: Nearly 80% (251) of the mothers had said that they initiate breast feeding after one hour of delivery, while only 6% initiated breastfeeding within one hour delivery. About 54% of the mothers were giving colostrum to their newborns, while others (45.86%) were giving pre-lacteal feeding to the infants including jaggery water and honey. It was observed that most (71.65%) of the mothers were continuing to breastfeed their children more than 18 months. Only 11.78% of the mothers started weaning before 6 months of age. Socio-economic status, literacy rate and working status of the mothers were some of the influencing factors. Conclusions: The study identified the practices of infant feeding, their determinants among the sugali tribes and recommendations to improve their practices. False beliefs and difficulties regarding breast feeding need to be addressed through heath education and family support.